Rancang Bangun Aplikasi Tracer Study Berbasis Website pada SMAN 1 Kutorejo di Kabupaten Mojokerto - Muhammad Alvin Agung Gumelar; Norma Ningsih; Tony Soebijono (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Tracer study is one way for schools or agencies to obtain graduate data that is used as input for improving the learning process. SMAN (State High School) 1 Kutorejo has conducted a tracer study since 2016 with an online system using the google form media. However, there are several problems regarding the current tracer study, including the absence of a special account created by the school, no real-time notification as a notification that the questionnaire has been filled out by alumni, and reports that require calculations are still using the formulation system through Microsoft. excel. Based on these problems, it is necessary. a tracer study system that includes login features, alumni data collection, questionnaire creation, questionnaire filling, real-time notifications and is also equipped with descriptive statistical methods for data presentation and waterfall method for the final project process. The results of this study are to help the counseling guidance of SMAN 1 Kutorejo obtain information about current alumni activities, find out information about the quality and teaching and learning facilities, and find out information about the quality of alumni. This information was obtained from questionnaires that had been prepared by the Counseling Guidance which were distributed and completed by alumni